Pendidikan Kesehatan dengan Media Film “Derita Tiada Akhir” Menggugah Pengantin Remaja dalam Menggunakan Kontrasepsi Modern - Tatik Kusyanti; Hadyana Sukandar; Farid Husin (Alma Ata University Press, 2016)
Adolescent marriage (10-19 years old) is a problem for every country, especially for developing countries. Based on the basic health research (Riskesdas), the adolescent marriage in Indonesia is 41.9% and this is the highest number compared with other age category. The number of adolescent marriage in West Java is in the second place after the middle of Kalimantan and the position is above the national number 50.2%. The number of adolescent marriage in Bandung is 23.9%, whereas the government target is only 3.5%. Adolescent marriage has a strong relationship with pregnancy and the high risk childbirth. This research goal was to analyze the usage and the impact of media film the risk of adolescent pregnancy on the modern contraceptive participation and those influencing factors. The research was conducted in the 7 offices of religion affairs (KUA) that spread in Bandung. This research is a quasi experiment research with post-test design and pre-post test design with total samples of 44 consisting of 22 bridal couple and 22 adolescent bridewomen that only registered their marriage in the 7 KUA’s. Adolescents marriage applicant samples were taken by consecutive sampling whereas the sampling for the adolescents that were married was taken by simple random sampling. Univariate analysis used frequency distribution and binomial, while bivariate analysis used chi-square and fisher’s exact, Multivariate analysis used Multiple Regresi Logistic. The research results show that reproductive health education about the adolescent pregnancy through film media could increase twice the participation of adolescent married couples in using modern contraception, by using chi square (p=0.015), RR:2.33 have the increase of reproductive health education. Based on the results, it can be concluded that reproductive health education through film media can increase the participation of adolescent married couples influenced the modern contraceptive participation.